Total Protein Content and Pathogenesis Related-Proteins in Leaf Intercellular Fluid of Cigar Tobacco Cultivar H-877 Infected with Tobacco Mosaic Virus (TMV) - Wiwiek Sri Wahyuni; Endang Budi Trisusilowati; Didiek Sulistyanto (Universitas Gadjah Mada, 1999)
The reaction of hypersensitive Nicotiana species or cultivar (N. glutinosa, N. tabacum cv. Xanthi nc., N. tabacum cv. H-877) to three isolates of TMV from Jember showed variable symptoms. Pattern of total protein from leaf was hard to distinguish between cultivar or species. The intercellular fluids (IF) of leaf tissues which contained pathogenesis related (PR) proteins of cigar tobacco cultivar H-877 (it derives the N-gene from N. glutinosa) has lost several protein bands than that of N. glutinosa. The H-382 cultivar which systemic reaction to TMV has a band with very low molecular weight, which was not detected in other species or cultivar infected with three TMV isolates. It seems there was an effect of longterm storage of leaf before IF-extraction to the resolution of some PR protein bands in SDS PAGE. Analysis of PR-proteins of H877 cultivar in 20-SDS PAGE showed it consist of b-4, b-5, b-6a, b-6b, b-7a, and b-8a proteins of Parent and Asselin(1984).